Optimization of cooling channel parameters for designing three plate mould of hexagonal floor tile using Taguchi method to reduce warpage - Mohd Adzwan, Md. Nor (2008)
This project deals with optimization of cooling channel parameters for designing three plate mould of hexagonal floor tile using Taguchi method to reduce warpage. The objective of this project is to analyze the hexagonal floor tile design by simulation with Moldflow Plastic Insight software (MPI) and to optimize the mould design parameter using Taguchi method. The product is designed in hexagonal shape build with interlocking features and will be used for application in indoor sports activities such as futsal, badminton, takraw and other sports. The material used for this design is thermoplastic elastomer (TPE) that increased the slipping resistance due to active and fast movement on it. The design of the product will be analyzed using MoldFlow Plastic Insight software (MPI) to reduce the warpage problem that appears during injecting the product. Warpage is the deflection of the part on the product design from its original shape. Taguchi method is used to optimize the parameter of the mould design for injecting the product with less warpage. In addition, the signal to noise ratio and analysis of variance is utilized to optimize the parameter for the product. The Taguchi method is conducted to minimize the warpage in both +z deflection and -z deflection. The result shown that, the most significance parameter of the mold design that tend to minimized the warpage values are from the cooling channel diameter at cavity half, cooling channel distance at core half and cooling channel diameter at core half. Also, from the result the summarized of the mold design parameter that reduces the warpage problem has been identified for the further process which is fabrication of mold.